行星传动系统的振动特性研究 - 陈俊锋; 刘晓辉; 谭长均 (Jixie chuandong)
Aiming at the failure problem of planetary transmission system due to the resonance in the process of actual application,by using 3D modeling software Pro/E a planetary transmission system entity model is established,the modal analysis of planetary transmission system is carried out by using Workbench,the inherent frequency and the vibration modes are obtained,and the vibration characteristic is analyzed.And through the research of sun gear floating and the influence of planet gear number on the vibration characteristics,further point out that the influence of planetary transmission system structure changes on vibration characteristics.The study of planetary transmission system design provides a basis for further improvement.